Multi-tiered systems of support for young children driving change in early education - Carta, Judith J.; Young, Robin Miller (Paul H. Brookes Publishing Co., 2019)
"This book addresses the process of designing, implementing, and ensuring sustainability of multi-tiered systems of support (MTSS) in early education settings. Chapters provide background about MTSS as well as descriptions of evidence-based practices designed to reduce the achievement gap before children enter kindergarten. The book is aimed at professionals planning for systems change in order to provide instruction that matches children's varying needs. Such professionals include directors and administrators in early childhood and early childhood special education, child care program directors, and Head Start administrators"--Provided by publisher.